Reproductive biology of Centaurea kilaea (Asteraceae, Cardueae) – an endemic species from Türkiye - Kartal, Ciler (Acta Botanica Croatica, 2025)
In this study, the embryology of Centaurea kilaea Boiss., a species endemic to Türkiye, was examined using light microscopy. The anthers of C. kilaea are tetrasporangiate; the anther wall development is dicotyledonous; and the tapetum is amoeboid. The meiotic division of the microspore mother cells is regular, and when the pollen grains are thrown from the anthers, they are three-celled. The ovary of C. kilaea is inferior, bicarpellary, syncarpous, and unilocular, which is characteristic of the Asteraceae family. It carries only a single ovule with basal placentation. The ovule is anatropous, unitegmic, and tenuinucellate. The megaspore mother cell undergoes meiotic division, giving rise to a linear tetrad of megaspores. The chalazal megaspore remains functional, and the other three megaspores degenerate rapidly. The functional megaspore undergoes three mitotic divisions in succession. As a result, a Polygonum-type embryo sac, with eight nuclei and seven cells, is formed. The antipodal cells persist until the first divisions of the zygote. In the mature embryo sac stage, the integument consists of the endothelium, peri-endothelial region, parenchymatous cells, and outer epidermis, from the inside out. Endosperm development is initially free nuclear, becoming cellular in the globular embryo stage. Embryo development is of the asterad type. The mature seed does not contain endosperm, but the endothelium persists.